An approach to carbon emission estimation for plant refurbishment strategies. Issue 3 (6th July 2010) - Tomlinson, Stuart; Wang, Chang J.; Morgan, Colin
The renewal or refurbishment of major items of electrical and mechanical equipment often imposes significant environmental cost, which may be quantified with reference to the relative quantity of carbon emissions. In order to fully assess environmental impact, determination of carbon emissions over the complete life cycle of such equipment is essential; however, the raw data necessary to produce accurate estimates are frequently found to be unreliable or sparse. In this paper, an approach to the estimation of carbon emissions for a particular electro-mechanical component, over its complete life cycle, is developed and methods of compensating for sparse data are proposed and assessed.